The effectiveness of teaching kurdish literature by using the flipped learning strategy in developing the skills of the quality of poetry recitation among seventh grade students: A research extracted from a doctoral dissertation, in progress - Abdullah, Nasreen; نبی , مولود (Humanities Journal of University of Zakho, 2024)
The present study aimed at investigating the effect of flipped classroom learning strategy on teaching Kurdish literature to the students of seventh grade in terms of poetry recitation. The authors adopted a quasi-experimental research design to conduct this study by utilizing pre and posttests. The population of the study were the female students of seventh grade at the morning basic schools at Directorate of Education of Western Duhok during the academic year 2021-2021. The study participants were from Nirnick and Bel schools for girls. The participants were randomly divided into an experimental group (consisted of 27 students) and a control group (consisted of 28 students). The experimental group was taught according to flipped classroom learning strategy and the control group was taught according to traditional teaching method. Moreover, a rubric including students’ skills at reciting poetry was designed. Twenty-two skills were included in the rubric and each skill was evaluated based on criteria describing it. The psychometric characteristics were also found for such skills. After conducting the experimental teaching which lasted for the whole semester, the data obtained from pre and posttests were analyzed using t-test. The results showed that flipped classroom learning strategy enabled the students in the experimental group to achieve better leaning in poetry recitation skills than the students in the control group. Furthermore, the authors forwarded some recommendations to the decision makers in the educational field and suggested more topics for future studies.